Health Related Nutritional Knowledge and Dietary Behavior Regarding Caffeine Intake among High School Students in Yongin Region - Kim, Seong Yeong (Osong Public Health Res Perspect, 2018)
OBJECTIVES: We aimed to examine health-related nutritional knowledge and dietary behavior related to caffeine intake among high school students (n = 310) in the Yongin region of Korea. METHODS: Data were collected using a face-to-face survey, and analyzed using chi-square test, t- test, and logistic regression analysis. RESULTS: The level of caffeine intake in respondents was divided into low (< 30 mg/d; n = 208) and high caffeine intake groups (> 30 mg/d; n = 102). Total nutritional knowledge related to bone disease was higher in the low intake group (score 2.75) than the high intake group (score 2.39; p < 0.05). The high intake group had lower scores for nutritional knowledge (score 0.70; p < 0.05) related to how caffeinated beverages affect sleep and for dietary behavior (score 3.25; p < 0.001), based on “I avoid caffeinated foods before sleep,” than the low intake group (nutritional knowledge score, 0.80; dietary behavior score, 3.76). CONCLUSION: In the overall analysis, the low caffeine intake group had better nutritional knowledge related to bone and sleep health, and healthier dietary behavior related to sleep health compared with the high intake group.